2018
DOI: 10.3892/ijmm.2018.4031
|View full text |Cite
|
Sign up to set email alerts
|

Corilagin induces apoptosis, autophagy and ROS generation in gastric cancer cells in�vitro

Abstract: Corilagin, a unique component of the tannin family, has been identified in several medicinal plants. In previous literature, corilagin exhibited a marked anticancer property in a variety of human cancer cells. However, the biological effects of corilagin on gastric cancer and the mechanisms involved remain to be fully elucidated. In the present study, it was reported that corilagin induced inhibition of cell growth in SGC7901 and BGC823 cells in a concentration-dependent manner. It was found that corilagin exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 48 publications
3
31
1
Order By: Relevance
“…It was confirmed that compound 18 could induce autophagy, apoptosis and ROS accumulation in gastric cancer cells in vitro [173]. IC50 values of HepG2, Molt-3, HL-60, NPC-BM1, HT 1080 and K562 were 1.42, 0.35, 0.12, 0.81, 1.02, 1.53 mg/mL in vivo , respectively [174].…”
Section: Biological Activitymentioning
confidence: 96%
“…It was confirmed that compound 18 could induce autophagy, apoptosis and ROS accumulation in gastric cancer cells in vitro [173]. IC50 values of HepG2, Molt-3, HL-60, NPC-BM1, HT 1080 and K562 were 1.42, 0.35, 0.12, 0.81, 1.02, 1.53 mg/mL in vivo , respectively [174].…”
Section: Biological Activitymentioning
confidence: 96%
“…The majority of patients relapse following surgery [113]. Xu and coworkers [114] studied the efficacy of corilagin on human gastric cancer cell lines (SGC7901 and BGC823) and suggested that it significantly inhibited cell proliferation, apoptosis, and autophagy. It was observed that corilagin fragmented poly (ADP ribose) polymerase (PARP, an indicator of caspase activation) and decreased the level of procaspase-8, procaspase-9, and procaspase-3 in BGC823 and SGC7901cells in a dose-dependent way, as detected by Annexin V/PI staining.…”
Section: Anticancer Activity Of Corilaginmentioning
confidence: 99%
“…Moreover, corilagin has been confirmed to exert a less toxic effect on normal human gastric mucosal epithelial cells (GES-1). Hence, corilagin could be a propitious agent for the cure and management of human gastric cancer [114].…”
Section: Anticancer Activity Of Corilaginmentioning
confidence: 99%
“…Similarly, Xu et al reported that corilagin [β-1-O-galloyl-3,6-(R)-hexahydroxydiphenoyl-D-glucose] induced the inhibition of gastric cancer cell (SGC-7901 and BGC-823) growth by activating apoptosis. Moreover, corilagin (10-30 µM) triggered autophagy, which had a cytoprotective effect [245].…”
Section: Phenolic Acidsmentioning
confidence: 99%